Der Wille des Menschen - Alttestamentliche Aspekte zur Debatte um die Freiheit und Unfreiheit menschlichen Wollens - Oorschot, Jürgen van (Kerygma und Dogma, 2018)
In which contexts does Old Testament literature refer to the human will? What are the capacities and limits of human will, and what role does this will play in the relationship to God? This article responds to these questions with reference to the systematic-theological debate about the free and unfree will since Martin Luther's De servo arbitrio.